2019
DOI: 10.1016/j.snb.2018.10.158
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum doped zinc oxide (AZO) coated optical fiber LMR refractometers—An experimental demonstration

Abstract: This work presents the experimental demonstration of lossy mode resonance generation by means of aluminum doped zinc oxide thin-films. The use of such material may allow to optimize the performance of LMR-based sensors, obtaining good sensitivity at lower costs than other overlays, such as those including indium. The refractometric response of the fabricated devices is explored in different spectral regions. One refractometer working in the near infrared region was fabricated, obtaining a sensitivity of 2,280 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The sensing mechanism for the PC-NCF is similar to that for the LMR structure and relies on the change of the thickness and refractive index contrast of the high-index coating and the intensity of the evanescent wave generated at the outer boundary of the coating layer [3,5,6]. Based on the theoretical analysis in this work, several methods of reducing the length of the PC-NCF in practical devices such as curvature sensors and optical filters exist.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The sensing mechanism for the PC-NCF is similar to that for the LMR structure and relies on the change of the thickness and refractive index contrast of the high-index coating and the intensity of the evanescent wave generated at the outer boundary of the coating layer [3,5,6]. Based on the theoretical analysis in this work, several methods of reducing the length of the PC-NCF in practical devices such as curvature sensors and optical filters exist.…”
Section: Discussionmentioning
confidence: 97%
“…OATING of optical fibers has been extensively studied as a key element of the design of various devices such as optical sensors [1][2][3][4][5][6][7][8][9][10], filters [11,12] and modulators [13]. Fiber coating materials include metals, metal oxides, graphene, polymers, and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical simulations reported a sensitivity of 3500 nm/RIU, increasing to 8500 nm/RIU with the utilization of a dual coating (AZO-TiO 2 ) [15]. Later, an experimental work showed the feasibility of the utilization of AZO for the generation of LMR-based refractometers by means of a 167 nm thin film [46]. This work showed the simultaneous generation of 3 LMR in the VIS-NIR range (visible and near-infrared spectrum), with a maximum sensitivity of 1153.6 nm/RIU for the lower-order resonance.…”
Section: Zinc Oxidementioning
confidence: 99%
“…ZnO and Ag nanolayers as well as their multilayer combination, due to their multifunctional properties such as band-gap tailoring, localized surface plasmon resonance effects, electrochemical stability, non-toxicity and suitability for doping are employed to coat the optical ber probe. [24][25][26][27] An Ag-ZnO nanocomposite coated on POF as an intensity modulated humidity sensor was reported by Jagtap et al They reported that the sensing mechanism is based on the adsorption of water molecules on the coated layer surface, which effectively results in changes in the boundary conditions due to the surface reactional cladding-guide interface and increases the beam connement in the ber which modulates the output intensity. 28 Therefore, the material selection and structure conguration of the coated nanostructure play a crucial role in the sensor performance.…”
Section: Introductionmentioning
confidence: 99%